La historia de los tarapaqueños peruanos repatriados a Lima (1907-1930) - Troncoso de la Fuente, Rosa (2025)
From 1907 until the late 1920s, hundreds of Peruvian Tarapacá residents, repatriated from the port of Iquique, disembarked in Callao. In Chile, they were attacked for being Peruvians; and in Lima, the joy of returning to their homeland was met with joblessness and housing shortages, insults, and attacks for “being Chileans.” As elderly citizens living in the Tarapacá urbanization in Callao, they told us their stories, among streets named after the saltpeter mines, which take us back to a rarely known story of patriotic love. This article is a tribute to their lives.